Enteral Feeding/Total Fluid Intake Ratio Is Associated With Risk of Bronchopulmonary Dysplasia in Extremely Preterm Infants - Lin, Bingchun; Xiong, Xiaoyun; Lu, Xia; Zhao, Jie; Huang, Zhifeng; Chen, Xueyu (Frontiers in Pediatrics, 2022)
Background: Nutrition is an essential factor in preventing and managing bronchopulmonary dysplasia (BPD), a multifactorial chronic respiratory disease in premature infants. This study examined the association between nutritional intakes during the first two weeks of life and BPD in extremely preterm infants. Methods: A retrospective single-center cohort study was performed in infants born <28 weeks’ gestational age or with a birth weight <1000g. Intake of energy and ratio of enteral feeding/ total fluid intake during the first two weeks of life and association with outcome of BPD were examined. Results: 134 infants were included in our study, and 43 infants (32.1%) developed BPD. The average of total caloric intake per day and the ratio of enteral feeding/ total fluid intake were significantly lower in the BPD group (total caloric intake：91.90 vs. 95.72 kcal/kg/d, p < 0.05, ratio of enteral feeding/total fluid intake: 0.14 vs. 0.18, p < 0.05), while the average of total fluid intake, caloric and protein intake from parenteral nutrition did not differ between the groups. The ratio of enteral feeding/ total fluid intake during the second week were significantly lower in the BPD group (0.21 vs. 0.28, p < 0.05), while this ratio during the first week did not differ between the groups. An increase of 10% in the ratio of enteral feeding/ total fluid intake during the second week of life significantly reduced the risk of BPD (OR 0.444, 95% CI: 0.270-0.731). Conclusions: A higher ratio of enteral feeding/ total fluid intake was associated with a lower risk for BPD. Early and rapidly progressive enteral nutrition should be encouraged in extremely preterm infants in the absence of feeding intolerance.